Perbandingan Pelaksanaan Pendidikan Seni di Dalam dan Luar Negeri - Ahmad Fauzan Yusman; Nurhizrah G; Azwar A; Rusdinal Rusdinal (Jurnal Ilmiah Wahana Pendidikan, 2021)
This article discusses how to compare the implementation of education, especially art education in the music sub-field at home and abroad. With a qualitative method with a descriptive analysis approach, researchers used observation and literature review. The implementation of art education is basically how to develop, provide opportunities and guide students in using their senses to be creative in solving problems. Music education abroad, such as Europe, Korea-Japan and America, is considered fast in the development of art education, especially music education. On the other hand, Indonesia, which has a wealth of culture, including a wealth of regional music, certainly has the opportunity to exist in the midst of a musical education style that tends to be oriented towards western music. Differences in the history of the nation at home and abroad, different methods and instruments also play a role in the development of music in each country.